Cardioplegia defibrillation of circulatory and metabolic phase ventricular fibrillation in a swine model() - Marill, Keith A. (Resuscitation, 2019)
INTRODUCTION: We previously found potassium cardioplegia followed by rapid calcium reversal (Kplegia) can achieve defibrillation in a swine model of electrical phase of ventricular fibrillation (VF) comparable to standard care. HYPOTHESIS: Exploring 3 possible potassium dose and timing protocols, we hypothesize Kplegia may benefit resuscitation of longer duration untreated VF. METHODS: Three separate blinded randomized placebo-controlled trials were performed with electrically-induced VF untreated for durations of 6, 9, and 12 min in a swine model. Experimental groups received infusion of 1 or 2 boluses of intravenous (IV) potassium followed by a single calcium reversal bolus. Potassium was replaced by saline in the control groups. Outcomes included: amplitude spectrum area (AMSA) during VF, resulting rhythms, number of defibrillations, return of spontaneous circulation (ROSC), and hemodynamics for 1 h post ROSC. Binomial and interval data outcomes were compared with exact statistics. Serial interval data were assessed with mixed regression models. RESULTS: Twelve, 12, and 8 animals were included at 6, 9, and 12 min VF durations for a total of 32. ROSC was achieved in: 4/6 Kplegia and 3/6 control animals in the 6 min protocol, (p = 1.00), 4/6 Kplegia and 2/6 control animals in the 9 min protocol,(p = 0.57), and 0/5 Kplegia and 1/3 control animals in the 12 min protocol, (p = 0.38). Two of 8 Kplegia animals achieved ROSC with chemical defibrillation alone. CONCLUSIONS: The majority of animals achieved ROSC after up to 9 min of untreated VF arrest using K plegia protocols. K plegia requires further optimization for both peripheral IV and intraosseous infusion, and to assess for superiority over standard care. Institutional Animal Care and Use Committee protocol #15127224.